2000
DOI: 10.15288/jsa.2000.61.688
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol's effects on sexual perception.

Abstract: Objective-This study examines hypotheses about alcohol's effects on sexual judgments based on both alcohol and misperception theories. It was hypothesized that gender, alcohol consumption and alcohol expectancy set would influence perceptions of sexuality. Method-Participants were unacquainted women and men (88 dyads) who interacted for 15 minutes within the context of the balanced placebo design. After the conversation ended, participants answered questions about their behavior and their partners' behavior. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
111
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 28 publications
5
111
1
3
Order By: Relevance
“…Therefore, they would perceive the woman as acting more sexually during the interaction and as being more sexually attracted to them than would other men. We also hypothesized that there would be an interaction between prior perpetration and alcohol consumption such that men who previously had committed sexual assault and drank alcohol would make the highest sexual ratings.In past misperception research, gender differences in perceptions of one's own and one's partner's behavior have been restricted to the sexual domain-differences have not been found in perceptions of friendliness (Abbey, 1982;Abbey et al, 2000). This research demonstrates that men who overattribute sexuality to their female partner are not simply rating her highly on all dimensions, they are focusing specifically on her sexuality.…”
mentioning
confidence: 70%
“…Therefore, they would perceive the woman as acting more sexually during the interaction and as being more sexually attracted to them than would other men. We also hypothesized that there would be an interaction between prior perpetration and alcohol consumption such that men who previously had committed sexual assault and drank alcohol would make the highest sexual ratings.In past misperception research, gender differences in perceptions of one's own and one's partner's behavior have been restricted to the sexual domain-differences have not been found in perceptions of friendliness (Abbey, 1982;Abbey et al, 2000). This research demonstrates that men who overattribute sexuality to their female partner are not simply rating her highly on all dimensions, they are focusing specifically on her sexuality.…”
mentioning
confidence: 70%
“…Research with college students has consistently found that men perceive women as behaving more sexually and as being more interested in having sex with them than the women actually are (Abbey, 1982;Abbey, Zawacki, & McAuslan, 2000;Harnish, Abbey, & DeBono, 1990). This finding is relevant to situational theories of sexual assault because some perpetrators may at least initially misperceive their female companion's cues.…”
Section: Men's Misperceptions Of Women's Sexual Intentionsmentioning
confidence: 99%
“…Thus, intoxication makes it very easy for a potential sexual assault perpetrator to interpret friendly cues as a sexual invitation if that is the behavior he is anticipating. Abbey et al (2000) examined the role of alcohol consumption in initial sexual misperceptions. Using the balanced placebo design (Rohsenow & Marlatt, 1981), unacquainted college men and women talked to each other for 15 min after drinking either an alcoholic or a nonalcoholic beverage.…”
Section: Alcohol Enhances Men's Misperception Of Women's Behavior-mentioning
confidence: 99%
“…For Nietzsche Mitleid is the enemy to be focused on because when it rules, and when suffering is seen as the greatest evil, "people lose the ability to endure hardship and privation as well as the attendant personal strength and resistance." 119 Mitleid "saps the capacity to inflict suffering as well as to endure it." 120 For Nietzsche, the achievement of greatness, especially in the unflinching pursuit of knowledge, which is his main concern in Dawn, "requires the ability to endure, inflict, and witness pain."…”
Section: An Epicurean Momentmentioning
confidence: 99%
“…120 For Nietzsche, the achievement of greatness, especially in the unflinching pursuit of knowledge, which is his main concern in Dawn, "requires the ability to endure, inflict, and witness pain." 121 As he puts it in Dawn 146, and where he presents the idea of a new ploughshare, "if, with regard to ourselves, we do not heed, in narrow, petty-bourgeois fashion, immediate consequences and sufferings: why should we have to do so with our neighbour?" 122 In making this sacrifice, in which we and our neighbours are included, the aim, he says, is to "strengthen and elevate the general feeling of human power (Macht)" and, in this way, seek to effect a positive increase in happiness.…”
Section: An Epicurean Momentmentioning
confidence: 99%